Dzielimy się Doświadczeniem Anterior ventricular aneurysm with concomitant postinfarction ventricular septal defect – case report - Żelazny, Piotr; Witt-Majchrzak, Anna; Buzun, Leszek; Pawlak, Sebastian; Szapiel, Grzegorz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Postinfarction ventricular septal defect is a relatively rare, but serious complication of myocardial infarction. Surgical repair remains the method of choice, although it is associated with very high mortality. We report a case of a 65-year-old patient with ventricular septal rupture coexisting with left ventricle anterior wall aneurysm. The patient was electively operated on with closure of ventricular septal rupture and simultaneous Dor-Menicanti procedure.